The Vitek analyser for routine bacterial identification and susceptibility testing: protocols, problems, and pitfalls. Issue 4 (April 1998) - Shetty, N; Hill, G; Ridgway, G L
Abstract : Automated and semiautomated technology in microbiology has seen great advances in recent years. The choice of automated equipment for the identification and susceptibility testing of bacteria in a routine diagnostic laboratory depends on speed, accuracy, ease of use, and cost factors. The Vitek analyser (bioMerieux, UK) was installed in a busy diagnostic teaching hospital laboratory in London. This report describes one year's experience. Changes to work practice as a result of incorporating the equipment into the laboratory, and the advantages and disadvantages of automation in key areas are described in detail, together with possible solutions to problems. The Vitek analyser was found to be valuable for the speed and accuracy with which results were available for the common bacterial pathogens. Results of susceptibility testing were standardised according to NCCLS guidelines and used breakpoint MICs to ascertain susceptibility and resistance; they were an improvement on disc testing. This equipment is not a reference facility for difficult to identify organisms and many manual techniques, including some disc susceptibility testing, will have to be retained by the laboratory.